2013
DOI: 10.1063/1.4795603
|View full text |Cite
|
Sign up to set email alerts
|

Modulation phenomena in Si nanowire field-effect transistors characterized using noise spectroscopy and gamma radiation technique

Abstract: High-quality silicon nanowire (NW) field-effect transistors (FETs) were designed and fabricated. Features of transport and modulation phenomena of the structures were studied using a number of techniques, including noise spectroscopy. Using the 1/f noise component level, the values of the volume trap densities in gate dielectric are estimated to be around 1 Â 10 17 cm À3 eV À1 . This result proves high quality of the investigated structures. Analysis of Lorentzian noise components of NW samples is used to char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…In this case, it is concluded that RTN in the front-oxide gives rise to this Lorentzian component. 27,36 Notice also the much higher amplitude of the noise PSD, confirming the role of RTN in enhancing the noise variability. In fact, in order to further clarify this issue, two-dimensional device simulations will be instructive to derive the front/back-gate and drain voltage dependence of the RTN and associated GR noise.…”
Section: Random Telegraph Noise and Deep-level Spectroscopysupporting
confidence: 63%
“…In this case, it is concluded that RTN in the front-oxide gives rise to this Lorentzian component. 27,36 Notice also the much higher amplitude of the noise PSD, confirming the role of RTN in enhancing the noise variability. In fact, in order to further clarify this issue, two-dimensional device simulations will be instructive to derive the front/back-gate and drain voltage dependence of the RTN and associated GR noise.…”
Section: Random Telegraph Noise and Deep-level Spectroscopysupporting
confidence: 63%
“…However, it was recently demonstrated that the low‐frequency noise in nanotransistor‐based biosensors can be successfully used as a useful signal . In particular, it has been shown that biosensors based on liquid‐gated nanowire FETs can demonstrate the random‐telegraph noise caused by the single trap phenomena . In this specific case, improved sensitivity to the analyte can be obtained by considering trapping‐detrapping noise as a useful signal .…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the generally accepted opinion that RTS fluctuations restrict the operation of ultimately scaled electronic devices, there are cases when they can be effectively used for fundamental studies as well as for applied purposes. The modulation effect caused by a single trap leads to RTS fluctuations of the channel conductivity. The ability to manipulate and monitor a single electron spin with a single center formed by a defect in the gate oxide of a silicon transistor was demonstrated using electron trapping statistics .…”
Section: Introductionmentioning
confidence: 99%